2008
DOI: 10.1002/dvdy.21624
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac expression of the drosophila Transglutaminase (CG7356) gene is directly controlled by myocyte enhancer factor‐2

Abstract: The myocyte enhancer factor-2 (MEF2) family of transcription factors plays key roles in the activation of muscle structural genes. In Drosophila, MEF2 accumulates at high levels in the embryonic muscles, where it activates target genes throughout the mesoderm. Here, we identify the Transglutaminase gene (Tg; CG7356) as a direct transcriptional target of MEF2 in the cardiac musculature. Tg is expressed in cells forming the inflow tracts of the dorsal vessel, and we identify the enhancer responsible for this exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 88 publications
0
10
0
Order By: Relevance
“…Tg is expressed in all Svp cells of the embryonic dorsal vessel (Iklé et al, 2008), and we found that this pattern of expression persisted until the adult stage in Tg-lacZ animals. In fillets of young transgenic adults stained for ß-galactosidase (ß-gal) activity, we observed five sets of cardial cells stained, spanning from the posterior of the thorax, to abdominal segment A5 (Figure 2A).…”
Section: Resultsmentioning
confidence: 64%
“…Tg is expressed in all Svp cells of the embryonic dorsal vessel (Iklé et al, 2008), and we found that this pattern of expression persisted until the adult stage in Tg-lacZ animals. In fillets of young transgenic adults stained for ß-galactosidase (ß-gal) activity, we observed five sets of cardial cells stained, spanning from the posterior of the thorax, to abdominal segment A5 (Figure 2A).…”
Section: Resultsmentioning
confidence: 64%
“…8) As a first step in the study on dTG functions, we established transgenic fly lines overexpressing dTG-A in various tissues and at various developmental stages utilizing a GAL4-UAS targeted expression system. Recently, we found that overexpression of dTG-A in the eye imaginal disc of Drosophila larvae caused a rough eye phenotype in adult compound eyes, and that the induced phenotype is probably due to the occurrence of apoptosis and enhancement of the JNK signaling pathway.…”
mentioning
confidence: 99%
“…5A). One transglutaminase ( Tg ) gene has been identified in Drosophila (CG7356) that appears to be expressed predominantly in cardiac tissue (Iklé et al, 2008) but whether this functions in the CNS remains unknown. It is tempting to hypothesize that inhibiting TG activity under conditions of excess 5-HT prevents neurotransmitter binding to cytoplasmic proteins that would initiate spheroid formation.…”
Section: Discussionmentioning
confidence: 99%